Interactions between radial electric field, transport and structure in helical plasmas - Katsumi Ida (Вопросы атомной науки и техники, 2006)
Control of the radial electric field is considered to be important in helical plasmas, because the radial electric field and its
shear are expected to reduce neoclassical and anomalous transport, respectively. Particle and heat transport, that determines the
radial structure of density and electron profiles, sensitive to the structure of radial electric field. On the other hand, the radial
electric field itself is determined by the plasma parameters. In general, the sign of the radial electric field is determined by the
plasma collisionality, while the magnitude of the radial electric field is determined by the temperature and/or density gradients.
Therefore the structure of radial electric field and temperature and density are strongly coupled through the particle and heat
transport and formation mechanism of radial electric field. Interactions between radial electric field, transport and structure in
helical plasmasis discussed based on the experiments on Large Helical Device. Управление радиальным электрическим полем в плазме винтовой установки имеет большое значение, потому
что электрическое поле и его шир должны снижать соответственно неоклассический и аномальный переносы.
Перенос частиц и тепла, который определяет радиальный профиль плотности, чувствителен к структуре радиального
электрического поля. С другой стороны, само радиальное электрическое поле зависит от параметров плазмы.
Вообще знак радиального электрического поля определяется столкновительностью плазмы, а его величина –
градиентами температуры и/или плотности. Поэтому структура радиального электрического поля тесно связана с
температурой и плотностью через перенос частиц и тепла и механизм формирования радиального электрического
поля. На основе экспериментов на LHD рассмотрено взаимодействие между радиальным электрическим полем,
переносом и структурой в плазме винтовой установки. Керування радіальним електричним полем в плазмі гвинтової установки має велике значення, тому що електричне поле та його шир повинні знижувати відповідно неокласичний і аномальний переноси. Перенос частинок та тепла, що визначає радіальний профіль густини, є чутливий до структури радіального електричного поля. З другого боку, саме радіальне електричне поле залежить від параметрів плазми. Взагалі знак радіального електричного поля визначається зіткненістю плазми, а його величина – градієнтами температури і/або густини. Тому структура радіального електричного поля тісно пов’язана з температурою і густиною через перенос частинок і тепла та механізм формування радіального електричного поля. На основі експериментів на LHD розглянуто взаємодію між радіальним електричним полем, переносом і структурою в плазмі гвинтової установки.